The Dutch wife - Keith, Ellen (Park Row Books, 2018)
"Amsterdam, May 1943. As the tulips bloom and the Nazis tighten their grip across the city, the last signs of Dutch resistance are being swept away. Marijke de Graaf and her husband are arrested and deported to different concentration camps in Germany. Marijke is given a terrible choice: to suffer a slow death in the labor camp or--for a chance at survival--to join the camp brothel. On the other side of the barbed wire, SS officer Karl Müller arrives at the camp hoping to live up to his father's expectations of wartime glory. But faced with a brutal routine of overseeing executions and punishments, he longs for an escape. When he encounters the newly arrived Marijke, this meeting changes their lives forever"--Provided by publisher.